PENGARUH HEALTHSCAPE TERHADAP BEHAVIORAL INTENTION YANG DIMEDIASI OLEH SERVICE QUALITY PADA RUMAH SAKIT HARAPAN BUNDA DI BANDA ACEH - Oshy Mora, Muhammad Basyir (Departemen Manajemen, 2018)
Abstract: This research wad conducted to measure the influence of Healthscape on Behavioral Intention with Service Quality as a mediation variable at Harapan Bunda Hospital in Banda Aceh. The sample used in this study is the citizen of Harapan Bunda Hospital who have been treated with the total of 110 respondents. The data collecting tool used in this research is questionnaire. Purposive sampling method is used for the sampling technique of this research. Hierarchical Linear Modeling (HLM) is used as an analytical method to determine the effect of all the variables involved. Based on the result of the HLM analysis, it indicates that Healthscape has positive effect on Behavioral Intention, Healthscape has positive influence on Service Quality, Service Quality has positive effect on Behavioral Intention, and Service Quality mediates Healthscape relationship to Behavioral Intention.Keywords: Healthscape, Behavioral Intention, Service Quality, Hierarchical Linear Modelling